Lectotypes for Tricolia pullus, Gibbula divaricata and Theodoxus fluviatilis (Mollusca, Gastropoda) Revisited - Anistratenko, V.V. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2005)
During the recent faunal and taxonomic revisions of the Ukrainian marine and freshwater Gastropoda, the lectotypes for some of the species studied have been designated. As the relevant information was published in Russian, its accessibility for the international scientific community is limited. The present communication includes the detailed description of the lectotypes for Tricolia pullus, Gibbula divaricata and Theodoxus fluviatilis and additional taxonomic remarks on the species. All lectotype designations are based on black-white photographs of syntypes stored in the Linnaeus collection at the Linnean Society of London (Great Britain). Most important taxonomic characters such as size, outline, spire angle, apertural size, shape, etc. could be deduced from the figures.